Can ankle anticipatory postural adjustments associated with gait initiation be modifiede in post stroke subjects submitted to a physiotherapy program? - Pereira, S. (2021)
Postural control is a complex ability of the central nervous system, fundamental prerequisite in several motor programs, that is often compromised after central nervous system injury, particularly in ischemic events involving the middle cerebral artery. Stroke in this territory frequently compromise cortical output from pre-motor and supplementary motor areas and their connectivity with subcortical structures such as reticular formation.